Risk factors for wasting in toddlers in East Nusa Tenggara - Shagti Indhira; Khomsan Ali; Dewi Mira; Latifah Melly (BIO Web of Conferences)
Background: Wasting is a significant public health issue in East Nusa Tenggara (NTT), Indonesia, and it negatively impacts the nutritional status of toddlers. Objective: This study aims to analyze the factors associated with wasting among toddlers in NTT. Method: This observational study employed a cross-sectional design, conducted from July to August 2023 at the Panite and Kualin Health Centers in TTS, NTT Province, with a total of 150 respondents. Chi-square tests were used to analyze the relationship between variables, and logistic regression was applied to identify risk factors. The prevalence of wasting in 2022 was 10.7%. Research Results: The findings indicate that toddlers with wasting have a higher proportion of shorter birth lengths (<48cm) at 17.3%, are less frequently given early breastfeeding initiation (18%), are more prevalent in families with a moderate number of members (5-6 people) at 23.3%, have mothers with no education (2.7%) or only elementary education (20.7%), and have mothers with low knowledge about nutrition and health (score<60) at 18%, compared to non-wasting toddlers. Statistically significant differences were observed for birth length (p=0.040), early initiation of breastfeeding (p<0.001), the first drink given at birth (p=0.035), number of family members (p=0.041), mother's education (p=0.023), and mother's knowledge about nutrition and health (p=0.020) between wasting and non- wasting toddlers. The most influential factors contributing to wasting in toddlers are the duration of exclusive breastfeeding, per capita income, and postnatal environmental factors. The variables analyzed in this study explain 36.1% of the factors affecting wasting among toddlers in East Nusa Tenggara. These findings highlight the need for a comprehensive approach to addressing wasting in the region, emphasizing improved breastfeeding practices, increased family income, and enhancements in postnatal environmental conditions.